A Critical Analysis of Language Variation In The Traditional Art Market Senggigi and Sade (Sociolinguistic Studies) - Wirata, I Wayan; Rahman, Arif (Yayasan Pendidikan Intan Cendekia, 2021)
The researcher interested in language variations that occur in the traditional markets of Senggigi West Nusa Tenggara and Traditional House of Sade. Thus, this study analyzes the language variations in the process of buying and selling in the realm of Senggigi traditional markets and Traditional House of Sade. The author conducted research by taking the title